2021
DOI: 10.1002/ajp.23271
|View full text |Cite
|
Sign up to set email alerts
|

The marmoset as an important primate model for longitudinal studies of neurocognitive aging

Abstract: Age-related cognitive decline has been extensively studied in humans, but the majority of research designs are cross-sectional and compare across younger and older adults. Longitudinal studies are necessary to capture variability in cognitive aging trajectories but are difficult to carry out in humans and long-lived nonhuman primates. Marmosets are an ideal primate model for neurocognitive aging as their naturally short lifespan facilitates longitudinal designs. In a longitudinal study of marmosets tested on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Within the comparative perspective of this Special Issue, the authors have addressed various aspects of the aging phenotype in wellcharacterized and emerging NHP models, ranging from prosimians to hominids, including: gray mouse lemurs (Chaudron et al 2021), common marmosets (Rothwell et al, 2021), vervet/African green monkeys (Frye et al, 2021), three macaque species: rhesus (Arnsten et al, 2021;Upright & Baxter, 2021), cynomolgus (Darusman et al, 2021), and Barbary (Rathke & Fischer, 2021); and chimpanzees (Mulholland et al, 2021). Four main themes emerge from this collection.…”
Section: Contributions Of the Articles In This Special Issuementioning
confidence: 99%
“…Within the comparative perspective of this Special Issue, the authors have addressed various aspects of the aging phenotype in wellcharacterized and emerging NHP models, ranging from prosimians to hominids, including: gray mouse lemurs (Chaudron et al 2021), common marmosets (Rothwell et al, 2021), vervet/African green monkeys (Frye et al, 2021), three macaque species: rhesus (Arnsten et al, 2021;Upright & Baxter, 2021), cynomolgus (Darusman et al, 2021), and Barbary (Rathke & Fischer, 2021); and chimpanzees (Mulholland et al, 2021). Four main themes emerge from this collection.…”
Section: Contributions Of the Articles In This Special Issuementioning
confidence: 99%
“…Another well‐known species of platyrrhine primate with biparental care used in laboratory studies is the marmoset ( Callithrix jacchus ). This species has become a desirable model for studying aging because its relatively short lifespan allows researchers to observe the same individuals across the lifespan (Rothwell et al, 2021). Like titi monkeys, but unlike many other primate species, marmoset fathers engage in high rates of paternal care, and research has shown that male survivorship is significantly longer than females in captivity (Nishijima et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Scientists are working to address these issues. In addition to a long history warning the field about the potential limitations to conducting comparative psychology with an anthropocentric lens (Eaton et al, 2018; Shettleworth, 1993; Vonk, 2021, this issue), there has been a recent slew of scientific articles defending the use of nonhuman animals in basic research ranging in topics from neuroscience to addiction to cognitive decline to mood disorders, among other areas (Barron et al, 2021; Ma et al, 2019; Phillips et al, 2014; Rothwell et al, 2021; Spanagel, 2017). Scientists are also actively engaging with their members of Congress, often with the support of the scientific societies they belong to, to educate them about the vital role of nonhuman animals, and comparative psychology, in the research enterprise and in answering outstanding questions about human and nonhuman animal health (American Psychological Association [APA], 2013, 2021).…”
Section: The Next 100 Years Of Comparative Psychologymentioning
confidence: 99%